Genetic reprogramming with stem cells regenerates glomerular epithelial podocytes in Alport syndrome - LeBleu, Valerie S.; Kanasaki, Keizo; Lovisa, Sara; Alge, Joseph L.; Kim, Jiha; Chen, Yang; Teng, Yingqi; Gerami-Naini, Behzad; Sugimoto, Hikaru; Kato, Noritoshi; Revuelta, Ignacio; Grau, Nicole; et al. (Life science alliance, 2024)
Glomerular filtration relies on the type IV collagen (ColIV) network of the glomerular basement membrane, namely, in the triple helical molecules containing the α3, α4, and α5 chains of ColIV. Loss of function mutations in the genes encoding these chains (Col4a3, Col4a4, and Col4a5) is associated with the loss of renal function observed in Alport syndrome (AS). Precise understanding of the cellular basis for the patho-mechanism remains unknown and a specific therapy for this disease does not currently exist. Here, we generated a novel allele for the conditional deletion of Col4a3 in different glomerular cell types in mice. We found that podocytes specifically generate α3 chains in the developing glomerular basement membrane, and that its absence is sufficient to impair glomerular filtration as seen in AS. Next, we show that horizontal gene transfer, enhanced by TGFβ1 and using allogenic bone marrow-derived mesenchymal stem cells and induced pluripotent stem cells, rescues Col4a3 expression and revive kidney function in Col4a3-deficient AS mice. Our proof-of-concept study supports that horizontal gene transfer such as cell fusion enables cell-based therapy in Alport syndrome.